(untitled) (Revista Brasileira de Contabilidade e Gestão, 2017)
This study aims to structure a complementary model for the analysis of traditional financial statements through integrated and structured approach to non-linear regression using degree of polynomial functions 2. For this, we selected a medium-sized company located in southern Brazil, whose financial statements for the period of the 20X0 20x4 served to calculate the liquidity ratios, capital structure, profitability and solvency, from which was prepared a future prediction or regression 20x5 20X6 through the degree of polynomial functions 2. The polynomial function can used by Microsoft Office Excel® software, widely diffused in the corporate environment. The results presented by the trend lines obtain, on average, a coefficient of determination of 0.8529, which expresses the accuracy or reliability of future projection of the indices and coefficients of 85.29%. Therefore, the analysis of financial statements together with the trend line, makes the analyst has an alarm mechanism when the forecast point to indices with critical values and identify past and future situation of the corporation. The traditional analysis of the financial statements cannot be ignored, however, the degree of subjectivity used in this process, including integrated analysis reduces subjectivity and gives greater reliability and greater precision in preparing its completion, providing decision makers with a vision proactive of events occurred before, being able to change the direction of the corporation.